Using a Genre-Based Approach for Differentiated Instruction to Enhance Students’ Writing Skills - Nofitasari Nofitasari; Sidik Indra Nugraha (Journal of Educational Sciences, 2025)
This study investigates the application of the Genre-Based Approach in differentiated instruction to enhance students' writing skills. It also examines students' responses to the implementation of this approach in developing their writing abilities. The research employs a qualitative methodology with a case study design. The research participants consist of an English teacher and 41 eighth-grade students. Data were collected through observation, interviews, and documentation. The results of the study indicate that the teacher applied the four stages of the GenreBased Approach, namely BKOF, MOT, JCOT, and ICOT, which were combined with differentiated learning in writing skills. The study also shows that students experienced an increase in motivation and confidence and shows active participation in the learning process. However, it is found a number of challenges in its implementation. For teachers, the challenge lies in the limited time available, as GBA learning requires a lengthy and gradual process. Meanwhile, the challenges faced by students are related to their individual limitations in English language proficiency, necessitating intensive guidance and additional support during the writing process. Overall, this study demonstrates that the integration of GBA and differentiated learning can create a more inclusive, focused, and student-centered writing learning process.